2016
DOI: 10.1007/s10750-016-2842-3
|View full text |Cite
|
Sign up to set email alerts
|

How to mitigate cyanobacterial blooms and cyanotoxin production in eutrophic water reservoirs?

Abstract: Cyanobacterial blooms and cyanotoxin production were studied for 2 years in four hydrologically modified lakes with nutrient-rich waters. We hypothesized that frequency of flushing may considerably influence cyanobacterial blooms. Abundance, biomass and diversity of cyanobacteria as well as cyanotoxins' variability and concentrations (by HPLC-PDA; -FLD) were determined. In two larger lakes, into which nutrient-rich water was supplied once a year, lower cyanobacterial species diversity, higher biomass of Microc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…These phytoplankton groups also have the ability to respond quickly to the availability of environmental resources because of potentially high growth rates. Pawlik-Skowronska and Toporowska (2016) showed that intensive and frequent flushing increased cyanobacteria species richness and biodiversity and lowered the biomass of Microcystis and Aphanizomenon in two hydrologically modified lakes despite their periodical supply with nutrient-rich river waters. ++++: dominant taxa (contribution >50% in the total phytoplankton abundance); +++: subdominant taxa (25-49%); ++: accompanying taxa (10-24%); +: 5-9%; s: spring, sr: summer; a: autumn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These phytoplankton groups also have the ability to respond quickly to the availability of environmental resources because of potentially high growth rates. Pawlik-Skowronska and Toporowska (2016) showed that intensive and frequent flushing increased cyanobacteria species richness and biodiversity and lowered the biomass of Microcystis and Aphanizomenon in two hydrologically modified lakes despite their periodical supply with nutrient-rich river waters. ++++: dominant taxa (contribution >50% in the total phytoplankton abundance); +++: subdominant taxa (25-49%); ++: accompanying taxa (10-24%); +: 5-9%; s: spring, sr: summer; a: autumn.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, some studies have shown that water level fluctuations (WLFs), water flushing time (Tf), and flow rate may explicitly or implicitly influence the abundance and composition of phytoplankton (Bailey-Watts, Kirika, May, & Jones, 1990; Leira & Cantonati, 2008, and references therein), including the cyanobacteria community (Carvalho et al, 2011;Padisák, Köhler, & Hoeg, 1999;Pawlik-Skowronska & Toporowska, 2016;Romo, Soria, Fernández, Ouahid, & Barón-Solá, 2013). A few reports (Leira & Cantonati, 2008, and references therein) have revealed that WLFs affect phytoplankton abundance, biomass, size structure, taxonomic composition, species diversity, and rate of community compositional change.…”
Section: Introductionmentioning
confidence: 99%
“…Lakes differ in water management. In Lakes Skomielno and Krzczeń, water loss occurs naturally by evaporation and the lakes are refilled twice a year (in spring and autumn) with water from the above mentioned canal (Suchora, 2012;Pawlik-Skowrońska and Toporowska, 2016). This process is controlled by the Regional Management Office for Irrigation and Water Systems in Lublin.…”
Section: Study Areamentioning
confidence: 99%
“…and the frequency of WLFs in Lakes Krzczeń, Tomaszne, and Skomielno were obtained from calculations based on watermark readings presented by Suchora (2012) and Pawlik-Skowrońska and Toporowska (2016) and were highest in Lakes Tomaszne and Krzczeń (Tab. 1).…”
Section: Sampling Identification and Enumeration Of Epiphytic Algaementioning
confidence: 99%
See 1 more Smart Citation